2020
DOI: 10.1155/2020/9743075
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Effects of Arteriovenous Thrombolysis Combined with Mechanical Thrombectomy on Efficacy and Neurological Function of Acute Cerebral Infarct Patients

Abstract: Objective. To investigate the effects of arteriovenous thrombolysis combined with mechanical thrombectomy on clinical efficacy, neurological function, and the changes of nerve injury markers of acute cerebral infarct (ACI) patients. Methods. A total of 143 cases with ACI admitted to our hospital from June 2017 to June 2019 were elected as research subjects. Among them, 69 cases of patients who received treatment of arteriovenous thrombolysis were considered as group A, and 74 cases of patients who received tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%